2019
DOI: 10.17219/dmp/103851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hydroxyapatite coating on the stability of endosseous implants in rabbit tibiae

Abstract: Background. A dental implant surface which would promote rapid and strong osseointegration is a key factor of success in modern implantology. To achieve this goal, different implant surface modifications are developed. A hydroxyapatite (HA) coating changing a bioinert titanium surface into bioactive is one of them. Objectives. The objective of the study was to investigate the effects on bone osseointegration in rabbits resulting from the application of a HA coating deposited on titanium endosseous implants usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…30 The bone area fraction occupancy increased from 2 to 4 weeks, but without significative difference between the HAnano ® , SLActive ® to TiUnite ® . Our results corroborate with those of previous studies assessing HA-coated implants in rabbit tibia after two weeks, 59 in dogs' sockets after four weeks, 60 and in the iliac crests of goats after four weeks. 61 In all these studies, the HA biomimetic coating was able to shorten the healing period of the implants by increasing the implant-bone interaction.…”
Section: Dovepresssupporting
confidence: 92%
“…30 The bone area fraction occupancy increased from 2 to 4 weeks, but without significative difference between the HAnano ® , SLActive ® to TiUnite ® . Our results corroborate with those of previous studies assessing HA-coated implants in rabbit tibia after two weeks, 59 in dogs' sockets after four weeks, 60 and in the iliac crests of goats after four weeks. 61 In all these studies, the HA biomimetic coating was able to shorten the healing period of the implants by increasing the implant-bone interaction.…”
Section: Dovepresssupporting
confidence: 92%
“…By April 2020, a total of 128 studies had been gathered and subsequently assessed by the reviewers. From these, 92 studies were removed due to their being in vitro trials, duplicates, systematic reviews, or irrelevant, leaving a total of 30 studies: 27 were carried out on animals [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] and 3 on humans [ 23 , 24 , 25 ] ( Figure 2 “Flowchart”). Table 3 and Table 4 provide a general description of the details of each study.…”
Section: Resultsmentioning
confidence: 99%
“…In animal studies, ISQ was reported by 2 studies [ 26 , 27 ], both of which showed an increase when HA and alumina bioactive surfaces were used. BIC was reported in 11 studies [ 28 , 29 , 30 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 49 , 50 , 51 ]; BIC and BA together—5 studies [ 28 , 32 , 35 , 36 , 39 ]; RTT was reported in a study using rat tibiae where machined Ti surfaces and HA coated surfaces were compared [ 48 ]; RE (microcomputed tomography) is reported in 2 studies [ 31 , 34 ], SF—in one study [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxylapatite has several medical applications in medicine and dentistry. It proved to have good osseointegration properties [16].…”
Section: Discussionmentioning
confidence: 99%